El consumo de la yuca fresca en los Departamentos de Atlantico, Bolivar, Cordoba y Sucre - Janssen, W. (International Center for Tropical Agriculture, 1984)
The results of a survey among 480 housewives of rural and urban centers in the departments of Atlantico, Bolivar, Cordoba, and Sucre (Colombia) on fresh cassava consumption are presented. The consumption of cassava and yam decreases from rural to urban areas due to factors related to deterioration. Cassava is of major importance for the rural consumer, being less important for the urban consumer. Cassava as food is relatively more important for the lower income groups than for the high-income groups. In general, cassava consumption decreased from 1980 to 1983, this reduction ranging between 9-46 percent. (CIAT)